Inhibition of xanthine oxidase in the acute phase of myocardial infarction prevents skeletal muscle abnormalities and exercise intolerance. Issue 3 (13th May 2020) - Nambu, Hideo; Takada, Shingo; Maekawa, Satoshi; Matsumoto, Junichi; Kakutani, Naoya; Furihata, Takaaki; Shirakawa, Ryosuke; Katayama, Takashi; Nakajima, Takayuki; Yamanashi, Katsuma; Obata, Yoshikuni; Nakano, Ippei; et al.
Abstract: Aims: Exercise intolerance in patients with heart failure (HF) is partly attributed to skeletal muscle abnormalities. We have shown that reactive oxygen species (ROS) play a crucial role in skeletal muscle abnormalities, but the pathogenic mechanism remains unclear. Xanthine oxidase (XO) is reported to be an important mediator of ROS overproduction in ischaemic tissue. Here, we tested the hypothesis that skeletal muscle abnormalities in HF are initially caused by XO-derived ROS and are prevented by the inhibition of their production. Methods and results: Myocardial infarction (MI) was induced in male C57BL/6J mice, which eventually led to HF, and a sham operation was performed in control mice. The time course of XO-derived ROS production in mouse skeletal muscle post-MI was first analysed. XO-derived ROS production was significantly increased in MI mice from Days 1 to 3 post-surgery (acute phase), whereas it did not differ between the MI and sham groups from 7 to 28 days (chronic phase). Second, mice were divided into three groups: sham + vehicle (Sham + Veh), MI + vehicle (MI + Veh), and MI + febuxostat (an XO inhibitor, 5 mg/kg body weight/day; MI + Feb). Febuxostat or vehicle was administered at 1 and 24 h before surgery, and once-daily on Days 1–7 post-surgery. On Day 28 post-surgery, exercise capacity and mitochondrial respiration in skeletal muscle fibres were significantly decreased in MI + Veh compared with Sham + Veh mice. An increase in damaged mitochondria in MI + Veh compared with Sham + Veh mice was also observed. The wet weight and cross-sectional area of slow muscle fibres (higher XO-derived ROS) was reduced via the down-regulation of protein synthesis-associated mTOR-p70S6K signalling in MI + Veh compared with Sham + Veh mice. These impairments were ameliorated in MI + Feb mice, in association with a reduction of XO-derived ROS production, without affecting cardiac function. Conclusion: XO inhibition during the acute phase post-MI can prevent skeletal muscle abnormalities and exercise intolerance in mice with HF.